Evaluation of Chicken Intestine Waste as a Feed Ingredient for Red Tilapia (Oreochromis Sp.) Juveniles - Latif, Kamil (2006)
This study was designed to evaluate the use of chicken intestine as a protein source for red tilapia juveniles (Oreochromis sp.). This study comprises two experiments. In experiment I, the effect of feeding two types of food each respectively containing boiled chicken intestine and raw chicken intestine on the growth of red tilapia juvenile, Oreochromis sp., were studied. The results showed that the food containing boiled chicken intestine give better growth for the fish compared to the one containing raw chicken intestine when used in a 100% substitution for fish meal. Based on the results of experiment I, the boiled chicken intestine was selected for experiment II and was incorporated into isonitrogenous (40% protein) and isocaloric (450 kcal GEI100g) diets to replace 25%, 50%, 75% and 100% substitution levels of the fish meal protein in the control diet. The test diets were fed to triplicate groups of red tilapia juveniles, twice a day, for 70 days. The results showed that increase in the proportion of boiled chicken intestine in the diets resulted in growth retardation. Percent total length gain was highest for fish that were fed with the control diet, followed by those fed with the diet that substituted 50% of the fish meal with boiled chicken intestine. Percent body weight gain, similarly, was highest for fish fed with the control diet, followed again by fish that were fed with the diet that substituted 50% of the fish meal with boiled chicken intestine. The results showed that red tilapia juveniles fed with the control diet gave the best growth compared with fish that were fed others diets. Nevertheless, boiled chicken intestine could still be used as a main protein source to replace up to 50% of fish meal. Beyond and above the 50% substitution of fish meal with boiled chicken intestine clearly, resulted in stunting growth.